The ergogenic effect of acute carnosine and anserine supplementation: dosing, timing, and underlying mechanism. Issue 1 (31st December 2022) - de Jager, Sarah; Blancquaert, Laura; Van der Stede, Thibaux; Lievens, Eline; De Baere, Siegrid; Croubels, Siska; Gilardoni, Ettore; Regazzoni, Luca G.; Aldini, Giancarlo; Bourgois, Jan G.; Derave, Wim
ABSTRACT: Background: Recent studies suggest that acute-combined carnosine and anserine supplementation has the potential to improve the performance of certain cycling protocols. Yet, data on optimal dose, timing of ingestion, effective exercise range, and mode of action are lacking. Three studies were conducted to establish dosing and timing guidelines concerning carnosine and anserine intake and to unravel the mechanism underlying the ergogenic effects. Methods: First, a dose response study A was conducted in which 11 men randomly received placebo, 10, 20, or 30 mg.kg −1 of both carnosine and anserine. They performed 3x maximal voluntary isometric contractions (MVC), followed by a 5 x 6 s repeated cycling sprint ability test (RSA), once before the supplement and 30 and 60 minutes after. In a second study, 15 men performed 3x MVCs with femoral nerve electrical stimulation, followed by an RSA test, once before 30 mg.kg −1 carnosine and anserine and 60 minutes after. Finally, in study C, eight men performed a high intensity cycling training after randomly ingesting 30 mg.kg −1 of carnosine and anserine, a placebo or antihistamines (reduce post-exercise blood flow) to investigate effects on muscle perfusion. Results: Study A showed a 3% peak power (p = 0.0005; 95% CI = 0.07 to 0.27; ES = 0.91) and 4.5% peak torque (p = 0.0006; 95% CI = 0.12 to 0.50; ES = 0.87) improvement on RSA and MVC, with 30 mg.kg −1 carnosine + anserine ingestion 60 minutes before the performance yielding the best results. Study B found no performance improvement on group level; however, a negative correlation (r = −0.54; p = 0.0053; 95% CI = −0.77 to −0.19) was found between carnosinase enzyme activity (responsible for carnosine and anserine breakdown) and performance improvement. No effect of the supplement on neuromuscular function nor on muscle perfusion was found. Conclusions: These studies reveal that acute ingestion of 30 mg.kg −1 of both carnosine and anserine, 60 minutes before a high intensity exercise, can potentially improve performance, such as short cycling sprints or maximal muscle contractions. Subjects with lower carnosinase activity, and thus a slower breakdown of circulating dipeptides, appear to benefit more from this ergogenic effect. Finally, neither the involvement of a direct effect on neuromuscular function, nor an indirect effect on recovery through increased muscle perfusion could be confirmed as potential mechanism of action. The ergogenic mechanism therefore remains elusive.